1975
DOI: 10.1161/01.cir.52.6.979
|View full text |Cite
|
Sign up to set email alerts
|

Observer agreement in evaluating coronary angiograms.

Abstract: The reliability of interpretation of coronary arteriography as a diagnostic tool was investigated in a sub-study of the VA Cooperative Study of Surgical Treatment for Coronary Arterial Occlusive Disease. Twenty-two physicians with varying levels of experience read 13 cine angiograms -- blind -- on two different occasions. Analysis of inter- and intraobserver variability showed that angiographic items about which observers were most inconsistent from one reading to the other had the largest interobserver disagr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
100
0
2

Year Published

1978
1978
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 417 publications
(112 citation statements)
references
References 2 publications
5
100
0
2
Order By: Relevance
“…The increase in the peak value Cmax, which theoretically is due to changes in the vascular volume, and the decrease in the time of arrival Tan when contrast reaches the sampling point are evident. A model for flow that relates these two measured variables to coronary blood flow is described in Appendix 1, where it is demonstrated that, under certain conditions, the CONTRAST PASS CURVE LAD BED (2) The calculation of Cmax, TW, and the Q parameter can be implemented by digital image processing after selective injection by contrast into the coronary artery. The calculated values are then used to determine the flow ratio at every point in the image and an image of these values is produced.…”
Section: Methodsmentioning
confidence: 99%
“…The increase in the peak value Cmax, which theoretically is due to changes in the vascular volume, and the decrease in the time of arrival Tan when contrast reaches the sampling point are evident. A model for flow that relates these two measured variables to coronary blood flow is described in Appendix 1, where it is demonstrated that, under certain conditions, the CONTRAST PASS CURVE LAD BED (2) The calculation of Cmax, TW, and the Q parameter can be implemented by digital image processing after selective injection by contrast into the coronary artery. The calculated values are then used to determine the flow ratio at every point in the image and an image of these values is produced.…”
Section: Methodsmentioning
confidence: 99%
“…Imaging in each view was continued until a 2000-count information density (counts/cm2) was reached in the most normal portion of the left ventricular myocardium. This was approximately equivalent to 300,000-400,000 total counts and usually required [7][8][9][10] minutes of acquisition time per view. All analog scintigraphic images were unprocessed and recorded on x-ray transparent film.…”
Section: Methodsmentioning
confidence: 99%
“…3 A wide variability of visual estimates of gravity also occurs, usually documented by different examiners, as demonstrated by comparative studies of quantitative angiography. 4,5 Recently, studies correlating angiographic estimates of severity of coronary stenoses with intravascular ultrasonography performed during cardiac catheterization also showed difficulties in those angiographic evaluations, including on the elucidation of discrepant aspects regarding function assessment methods, such as myocardial perfusion scintigraphy. 6 Despite these limitations, angiography remains not only the gold-standard method, but also the most used and preferred method in determining approaches related to revascularization resulting from coronary lesions.…”
mentioning
confidence: 99%